Monetary disinflation with inflation inertia: Central bank autonomy in an open economy - Whitwell, Jan (School of Management Working Papers, 1995)
This paper draws on the strategic policy literature to model the optimal disinflation trajectory for an economy subject to external shocks and where the inflation process is characterised by a degree of expectational and externally-sourced inertia. In particular, it shows that the optimal inflation rate will converge on an interval bounded by the targetted rate and by the rate of externally-sourced inflation. Moreover, the point of convergence will vary with the openness of the economy, with the degree of wage flexibility, and with the relative weight given to the inflation objective. The policy implications of these results are examined with some reference to the New Zealand institutional environment and the disinflation of the post-1984 period. New Zealand did not adopt a disinflationary policy stance until late 1984, at a time when most other OECD countries were already well down their disinflation paths. As if to compensate for the late start, and in anticipation of the ratifying legislation, the Reserve Bank of New Zealand narrowed its macro-policy focus to a single objective - inflation. The Reserve Bank of New Zealand Act 1989 subsequently set "stability in the general level of prices" (currently defined in terms of maintaining an absolute target for consumer price inflation of O to 2 percent) as the primary macro-objective for monetary policy and freed the Bank from day-to-day political directives on the implementation of policy. The legislation has generated a vigorous Antipodean debate about optimal monetary policy in a small, open economy. This paper provides a theoretical underpinning for the contention that, in general, monetary disinflation under the Reserve Bank Act is a sub-optimal strategy.